Efeito do polimorfismo Thr92Ala da enzima desiodase tipo 2 no comportamento adaptativo de indivíduos com Transtorno do Espectro Autista - Marcondes, Alyna Araújo e (2018)
Thr92Ala D2 it’s the polymorphism of a thyroid hormone enzyme responsible to convert T4 in its active form, T3. This polymorphism has been related to Schizophrenia, Depression and Alzheimer’s disease, and its been shown that in the presence of both polymorphic alleles there’s a difference in the expression of genes relates to neurodegenerative process and oxidative stress in Central Nervous System (CNS). Studies with Autism Spectrum Disorder (ASD) patients has demonstrated that in this group, cells are more likely to present oxidative stress condition. The aim of this study was to evaluate whether ASD patients expressing Thr92Ala-D2 polymorphism would have poorer results at cognitive and behavioral tests when compared with patients without the polymorphism. Were assessed 132 ASD patients and the results of Autism Behavior Checklist (ABC), Vineland Scale of Adaptative Behavior, IQ and Autism Treatment Evaluation Checklist (ATEC). The analyses showed that patients expressing the polymorphism had better performances in Communication, Receptive Communication, Daily Living and Selfcare, although patients with wild genotyping and more critical ABC results had significative improvement of their social skills after interventions. Therefore, the existence of polymorphism improves adaptative performance in ASD patients, however the polymorphism seems to impair patient’s response to therapies. More researches are necessary in order to improve the comprehension of enzyme’s role and mechanisms underlying polymorphism’s CNS fingerprint.